2013
DOI: 10.4037/ajcc2013447
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Support System and Incidence of Delirium in Cognitively Impaired Older Adults Transferred to Intensive Care

Abstract: Background Elderly patients with cognitive impairment are at increased risk of developing delirium, especially in the intensive care unit. Objective To evaluate the efficacy of a computer-based clinical decision support system that recommends consulting a geriatrician and discontinuing use of urinary catheters, physical restraints, and unnecessary anticholinergic drugs in reducing the incidence of delirium. Methods Data for a subgroup of patients enrolled in a large clinical trial who were transferred to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…However, a recently published randomised controlled clinical trial of a multifaceted CCDSS intervention in hospitalised older adults with cognitive impairment demonstrated no improvement in the process of care; the intervention involved a CCDSS that alerted physicians on the presence of cognitive impairment, recommended referral to a geriatric consult and suggested discontinuation of catheterisation, physical restraints and anticholinergic medications . A sub‐analysis of this study, found that patients transferred to intensive care for delirium also did not see a change in prescribing patterns or decreasing incidence of delirium with the intervention . The main difference between these studies and others is that the CCDSS intervention did not involve a previously validated anticholinergic scale.…”
Section: Interventions To Reduce Anticholinergic Burden In Older Adultsmentioning
confidence: 65%
“…However, a recently published randomised controlled clinical trial of a multifaceted CCDSS intervention in hospitalised older adults with cognitive impairment demonstrated no improvement in the process of care; the intervention involved a CCDSS that alerted physicians on the presence of cognitive impairment, recommended referral to a geriatric consult and suggested discontinuation of catheterisation, physical restraints and anticholinergic medications . A sub‐analysis of this study, found that patients transferred to intensive care for delirium also did not see a change in prescribing patterns or decreasing incidence of delirium with the intervention . The main difference between these studies and others is that the CCDSS intervention did not involve a previously validated anticholinergic scale.…”
Section: Interventions To Reduce Anticholinergic Burden In Older Adultsmentioning
confidence: 65%
“…Another CDSS intervention was described in 2 articles: 1 article evaluated the implementation at the initial site, and 1 article evaluated the implementation at 4 sites [ 28 , 29 ]. Finally, 1 CDSS intervention was linked in 2 articles: 1 article described a subgroup analysis of the earlier RCT [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…[2428] A characteristic feature of all the studies is a significant representation of the African-American community with up to 50% of study subjects representing the minority race. In 2009, Indiana University Delirium working group consisting of IUCAR and the Pulmonary/ Critical Care division of Indiana University started a randomized, clinical trial known as the “Pharmacological Management of Delirium (PMD)” study.…”
Section: Methodsmentioning
confidence: 99%